2022
DOI: 10.1039/d1sm01647d
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation dynamics in deformable droplets

Abstract: Phase separation can drive spatial organization of multicomponent mixtures. For instance in developing animal embryos, effective phase separation descriptions have been used to account for the spatial organization of different...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…S12 in ESI and Supporting Video 4 † ). 54 This phenomenon indicates that the occurrence of phase separation is independent of the initial shapes of the droplets.…”
Section: Resultsmentioning
confidence: 93%
“…S12 in ESI and Supporting Video 4 † ). 54 This phenomenon indicates that the occurrence of phase separation is independent of the initial shapes of the droplets.…”
Section: Resultsmentioning
confidence: 93%
“…First, much of the past work on cellular unmixing focused on already differentiated cells [47]. However, if all cells kept their initial differentiation state over time, flows driven by differential tissue tensions may at some point cease [46]. However, the cells in our system are in the process of differentiating, and the observed recirculating flows are maintained over several hours, which makes us wonder whether the flows might be maintained through patterned cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our work shows for the first time that differential tissue surface tensions can drive long-range hydrodynamic flows that are maintained over a long time ( > ∼ 10 hours). In previous work, some of us have shown that such long-range flows can be important to substantially accelerate cellular unmixing [46].…”
Section: Discussionmentioning
confidence: 99%
“…Besides theoretical frameworks, [211,212] this consideration indicates the desperate need for continuum modeling that accounts for thermodynamic parameters while calculating hydrodynamics to bridge the gap between the individual sequences and macroscopic dynamic behaviors of DNA droplets. [214,215] Such numerical modeling could extract experimentally unachievable quantitative data as well as high-resolution visualization of dynamically restructuring DNA droplets in response to stimuli.…”
Section: Beyond Coarse-grained Modelingmentioning
confidence: 99%